Diffuse malignant epithelial peritoneal mesothelioma in pregnancy. A case report and literature review - (:unkn) unknown (I R O G CANADA, INC, 2004)
A 33-year-old pregnant woman of 38 weeks' gestation with massive peritoneal ascites presented. A cesarean section was performed and a viable 3,100 g male infant was delivered. Biopsy of the nodular enlargements from the omentum revealed a malignant epithelial peritoneal mesothelioma. Malignant mesothelioma is a rare malignancy which has not been described in term pregnancy and appears to be unaffected by the pregnant state.
Keywords: diffuse malignant epithelial peritoneal mesothelioma; pregnancy; histochemistry; immunohistochemistry; IMMUNOPEROXIDASE; ADENOCARCINOMA; CHEMOTHERAPY; SURVIVAL; MARKER; WOMEN; LUNG